Comparative clinical study evaluating the effect of adding Vildagliptin versus Glimepiride to ongoing Metformin therapy on diabetic patients with symptomatic coronary artery disease. (December 2020) - Werida, Rehab; Kabel, Mahmoud; Omran, Gamal; Shokry, Ahmed; Mostafa, Tarek
Abstract: Background and Objective: Cardiovascular diseases (CVDs) remain the most identified cause of death in patients with diabetes mellitus (DM). This study aimed to evaluate the effect of adding Vildagliptin versus Glimepiride to ongoing Metformin on the biomarkers of inflammation, thrombosis, and atherosclerosis in T2DM patients with symptomatic coronary artery disease (CAD). Methods: This study included 80 patients with uncontrolled T2DM and symptomatic CAD who were randomized to add either Vildagliptin 50 mg/day "group I" or Glimepiride 4 mg/day "group II" to ongoing Metformin therapy (1000 mg/day). Blood samples were collected at baseline and 3 months after intervention for biochemical analysis of HbA1c %, IL-1β, adiponectin, hsCRP and lipid profile. Additionally atherogenic index (AI) and coronary risk index (CRI) were determined. Results: Three months after intervention and as compared to group II (Glimepiride/Metformin), group 1 (Vildagliptin/Metformin) showed significantly lower BMI (28.73 ± 3.48 versus 30.55 ± 3.15; p = 0.02), HbA1c (6.05 ± 0.72 versus 7.06 ± 0.89; p < 0.0001), hsCRP (0.96 ± 0.20 versus 1.72 ± 0.38; p < 0.0001), IL-1β (34.95 ± 10.01 versus 45.13 ± 10.26; p < 0.0001), TC (136 ± 23.45 versus 169 ± 35.72; p < 0.0001), TG (116 ± 29.10 versus 146 ± 56.58; p = 0.005), and CRI (2.47 ± 0.90 versus 3.65 ± 1.19; p < 0.0001) which was associated with significantly higher adiponectin and HDL-C (4.42 ± 1.29 versus 2.52 ± 1.86; p < 0.0001 and 61 ± 23.04 versus 48 ± 12.92; p = 0.003 respectively). Conclusion: In patients with T2DM and symptomatic CAD, the addition of Vildagliptin to ongoing metformin showed better glycemic control, lower inflammatory markers (IL-1β and hsCRP), higher protective markers (adiponectin and HDL-C) and improved lipid profile compared to Glimepiride/metformin therapy.